ASUHAN GIZI PADA IBU HAMIL DENGAN HIPEREMESIS GRAVIDARUM - Wiwin Efrizal (Jurnal Gizi Prima (Prime Nutrition Journal), 2021)
Background : Hyperemesis gravidarum is a condition of nausea and vomiting that causes weight loss in pregnant women. Hyperemesis can cause malnutrition in the mother and affect the fetus and risk causing death. Purpose : The purpose of writing is to provide a comprehensive description of nutritional care for pregnant women with hyperemesis gravidarum using the literature review method. From the study, it is known the importance of proper nutritional care for mothers with hyperemesis gravidarum in the form of a cycle of assessment, nutritional diagnosis, intervention, monitoring and evaluation which are carried out continuously to overcome the problem of hyperemesis gravidarum in collaboration with the nutrition care team. Conclusion : The conclusion is that nutritional care with a comprehensive understanding of the problem of hyperemesis gravidarum in the form of cross-professions collaboration will improve the nutritional status of mothers.